Memory Aids as an Augmentative and Alternative Communication Strategy for Nursing Home Residents with Dementia. - Bourgeois, Michelle S.; Dijkstra, Katinka; Burgio, Louis; Allen-Burge, Rebecca (AAC: Augmentative & Alternative Communication, 2001)
The effect of memory aids on conversations between nursing aides and residents with dementia during 5-minute conversations was examined. Nursing home units in seven nursing homes were randomly assigned to treatment and control conditions. Residents in the treatment condition were given 12-page memory books consisting of autobiographical, daily schedule, and problem resolution information. Their assigned nursing aides were trained to use the memory books during care interactions and throughout the day. The duration and quality of verbal interactions between dyads of a resident and their nursing aide during 5-minute conversations were measured pre-and post-treatment using computer-assisted observational techniques and verbatim transcriptions of videotaped conversations (N = 66; 33 treatment dyads and 33 control dyads). The results revealed improvements on a variety of quantitative conversational measures (e.g., duration of speaking time, frequency of utterances) between treatment and control conditions as a function of memory book use. Similarly, the quality of conversations, as measured by the frequency of discourse characteristics (e.g., facilitative behaviors), improved as a function of memory book use for treatment dyads. Nursing aides' judgment of residents' depressive symptoms improved with memory aid use, suggesting changes in resident quality of life as a result of an AAC technique that enhanced information sharing and social closeness.